1975
DOI: 10.1037/0022-006x.43.6.780
|View full text |Cite
|
Sign up to set email alerts
|

Profile analysis and the abbreviated Wechsler Adult Intelligence Scale: A multivariate approach.

Abstract: The Satz-Mogel abbreviated Wechsler Adult Intelligence Scale (WAIS), while yielding high correlations with the standard WAIS scales, has been criticized for introducing sufficient subtest unreliability to prohibit profile interpretations. Using multivariate profile analytic techniques (Cattell's r p and hierarchical grouping analysis) and sampling from both brain-injured and psychiatric populations, these forms were compared in terms of overall pattern similarity and actuarial classification agreement. For bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…High consistency of our results with those reported in the literature suggests only little loss of information related to our use of the Satz-Mogel short form. In fact, high correlations between the full and short forms were demonstrated in the literature (Goebel & Satz, 1975;Marsh, 1973;Osato, Van Gorp, Kern, Satz, & Steinman, 1989). These findings justify the use of the Satz-Mogel short form as an alternative to the full version.…”
Section: Discussionmentioning
confidence: 96%
“…High consistency of our results with those reported in the literature suggests only little loss of information related to our use of the Satz-Mogel short form. In fact, high correlations between the full and short forms were demonstrated in the literature (Goebel & Satz, 1975;Marsh, 1973;Osato, Van Gorp, Kern, Satz, & Steinman, 1989). These findings justify the use of the Satz-Mogel short form as an alternative to the full version.…”
Section: Discussionmentioning
confidence: 96%
“…Administration of the Wechsler Abbreviated Scales of Intelligence [Goebel and Satz, 1975] estimated verbal IQ to be 55, performance IQ 62, and full scale IQ 55. Physical exam revealed mildly elevated blood pressure, mild facial dysmorphia (consisting of deep‐set eyes, a prominent nasal tip with prominent philtral ridges, myopathic facial appearance, full everted lower lip, and mildly deficient ear lobules: Fig.…”
Section: Clinical Reportmentioning
confidence: 99%
“…T. Watkins and Kinzie (1970) also concluded that Satz and Mogel's (1962) short form "may often be inappropriate for that very function for which all of the subtests were retained-profile analysis" (p. 345) but for somewhat different reasons: The scatter was significantly greater on the short form than on the original scale, and on average, there was only a moderate degree of correlation between a subject's subtest scores on the short form and those on the original scale. Goebel and Satz (1975) responded to those criticisms by making use of two special types of profile analysis that they believed were more meaningful than the techniques previously used, and they found that, on average, the profiles of a subject's subtest scores on Satz and Mogel's short form and on the original scale were highly similar and that the short form classified patients into approximately the same profile types as did the original scale. Goebel and Satz concluded that the short form could be substituted for the original scale "for both general IQ assessment.…”
Section: Specific Criticisms Of Short Formsmentioning
confidence: 99%